Association of Interleukin-6–174G/C Polymorphism With Ischemic Stroke: An Updated Meta-Analysis - Chai, Jie; Cao, Xian-Ling; Lu, Feng (Frontiers in Neurology, 2022)
Background: Although numerous epidemiological studies have investigated the association between −174G/C(rs1800795) polymorphism in the interleukin-6 (IL-6) gene-stimulatory region and the risk of ischemic stroke (IS), they failed to reach a unified conclusion. The true relationship between −174G/C(rs1800795) polymorphism and IS remains controversial and unclear. Therefore, in this meta-analysis, we aimed to analyze more precisely the association between −174G/C(rs1800795) single-nucleotide polymorphism (SNP) of IL-6 gene and IS in a larger pooled population. Methods: A comprehensive literature search was performed in PubMed, Web of Science, and the Cochrane Central Register of Controlled Trials until June 30, 2021. A fixed or random-effects model was utilized based on heterogeneity between studies. The odds ratios (ORs) and 95% confidence intervals (Cis) were calculated in the models of allele comparison (G vs. C), homozygote comparison (GG vs. CC) and (GC vs. CC), dominant (GG vs. GC + CC), hyper dominant (GG + CC vs. GC), and recessive (GG + GC vs. CC) to determine the strength of associations. Results: This meta-analysis included 13 case-control studies in 35 articles with 5,548 individuals. Overall, no significant associations between IL-6 −174G/C(rs1800795) and IS were identified (G vs. C:OR [95% CI] = 0.99 [0.81, 1.21], P = 0.91; GG + CC vs. GC:0.97 [0.85, 1.11], P = 0.66; GG vs. GC + CC: 1.01 [0.81, 1.25], P = 0.94; GC vs. CC: OR [95% CI] = 1.01 [0.68, 1.5], P = 0.96; GG vs. CC:0.93 [0.57, 1.51], P = 0.76; GG + GC vs. CC:0.97 [0.64, 1.47], P = 0.89). In the subgroup analyses by ethnicity or HWE P-value, there was a statistically significant association between IL-6 −174G/C(rs1800795) polymorphisms and IS in the alleles model; (G vs. C: LogOR [95% CI] = 0.14 [−0.16,.45], P = 0.00), homozygote model (GG vs. CC: LogOR [95% CI] = 0.18 [−0.58,.95], P = 0.00) and (GC vs. CC: LogOR [95% CI] = 0.2 [−0.46,.85], P = 0.00), dominant model (GG vs. GC + CC: OR [95% CI] = 0.02 [−0.72, 0.77], P = 0.00), and recessive model (GG + GC vs. CC: OR [95% CI]= −0.17 [−0.86,.52], P = 0.00) of the European population and in the dominant model (GG vs. GC + CC: OR [95% CI] = −0.13 [−0.51, 0.24]) of the Asian population. No statistical significance was identified in both six models of HWE p ≥ 0.2 group (both P ≥ 0.05). Conclusion: This meta-analysis revealed no correlation between IL-6 −174G/C(rs1800795) polymorphism and IS, whereas the subgroup analysis indicated that the relationship between IL-6 −174G/C(rs1800795) polymorphism and IS susceptibility varied significantly according to ethnicity and geography.